Identification of Challenges and Hazards associated with Cruise Traffic and Evacuation in the Arctic - Dalsand, Raymond; Nese, Tord (UiT The Arctic University of Norway, 2016)
Arctic cruise tourism is gaining in popularity. There is a need to better understand hazards that are connected with cruise traffic and evacuation in the Arctic. The Polar Code tries to enhance the safety of persons travelling in polar waters by giving functional requirements to life-saving appliances. However, it is unclear what is needed to achieve the required functionality, and how existing life-saving appliances perform compared to the requirements in the Polar Code. This thesis looks to present the challenges associated with cruise traffic in the Arctic, the main hazards associated with evacuation in an arctic environment, and what the possible gaps are between the current life-saving appliances and the level of safety the Polar Code tries to ensure. Based on a literature review, a risk analysis and a practical test, the thesis presents a review of arctic region characteristics, historical accidents, regulations and existing life-saving appliances. It also presents a description of the main hazards associated with evacuation from a cruise ship in an arctic environment, and the corresponding gaps between the performance of existing life-saving appliances and the level of safety the Polar Code tries to ensure. The challenges, hazards and gaps are discussed through incorporating results from the literature review, the risk analysis and the practical test. The thesis also highlights the contributions the authors provided to the SARex project through a preliminary hazard analysis, leading risk assessments prior to the practical test, actively participating in the test and documenting the workshop that summarized the experiences from the test.